Scaffolding on the use of loose parts in post-pandemic learning for age 5-6 years old - Fatiya Hanif; Avanti Vera Risti Pramudyani (Journal of Early Childhood Care and Education, 2023)
Scaffolding in early childhood learning is one of the teachers' efforts in optimizing the development of children to comply with ZPD (Zona Proximal Development). This research aims to know the form of scaffolding performed by teachers in the use of Loose Parts media consisting of four stages, namely exploration, experimentation, creative and building the meaning and purpose of playing during the learning process at Integrated Early Childhood Education (PAUD Terpadu) Aisyiyah Nur’aini unit two Yogyakarta. The method used qualitative descriptive approach. The research subjects were 15 teachers with 4 teachers as informants selected through purposive sampling techniques.  The researchers used triangulation techniques for data validation and Miles and Huberman models for data analysis. The research tools used are an unstructured interview guide, an observation guide, and a documentation guide. Research results show scaffolding on the use of Loose Parts media in learning related exploration stage, experimental stage, creative stage and stage building meaning and play objectives adapted to the objectives of each stage and condition of the child. All these stages are related to each other. Later on this study, it was found that learning at PAUD Terpadu Aisyiyah Nur’aini unit two Yogyakarta began to be directed using learning with the concept of the project, the Reggio Emilia model and mixed with literacy-based learning. With this research, it is hoped that teachers can provide the right scaffolding for the child during play activities so that the child's creativity develops optimally.